Synthesis of diethyl carbonate from CO2 and orthoester promoted by a CeO2 catalyst and ethanol. (January 2022) - Putro, Wahyu S.; Munakata, Yusuke; Ijima, Seiichiro; Shigeyasu, Shinji; Hamura, Satoshi; Matsumoto, Seiji; Mishima, Takayoshi; Tomishige, Keiichi; Choi, Jun-Chul; Fukaya, Norihisa
Graphical abstract: The combination of CeO2 catalyst and ethanol produced diethyl carbonate from CO2 and orthoester with high productivity. Highlights: CeO2 catalyzes DEC formation from CO2 and orthoester. Combination of CeO2 and ethanol promotes DEC yield. The CeO2 catalyst was recyclable with various orthoesters. Alkyl substituents of the orthoesters remarkably affect DEC yield. Abstract: The combination of a CeO2 catalyst and ethanol effectively promotes the direct synthesis of diethyl carbonate (DEC) from CO2 and an orthoester. The reaction temperature, initial CO2 pressure, and the ethanol/orthoester volume ratio were found to significantly influence DEC formation and were systematically studied to determine the optimum conditions. DEC amount of 5.2 mmol was obtained at 160 °C, 5 MPa of CO2, and a reaction time of 20 h, providing high productivity (1.21 mmolDEC mmolcatalyst −1 h −1 ) using a CeO2 catalyst. The recovered CeO2 catalyst was recyclable at least four times without any significant loss of activity when both triethyl orthoacetate and triethyl orthovalerate were used. A series of orthoesters bearing various alkyl substituents, aromatic substituents and halide moieties were evaluated for their activities with and without ethanol. In the presence of ethanol, orthoesters bearing longer alkyl substituents led to higher DEC yields, and orthoesters bearing aromatic and halide moieties negatively impacted DEC formation. In the absence of ethanol, triethyl orthoacetate provided the highest DEC yield; in all cases, the use of ethanol resulted in a greater DEC formation than when the reaction was performed without ethanol.